Analysis of Changes in Area of Mangrove Density at Ngurah Rai Bali Grand Forest Park Using Image of Landsat 8 Satellite - Darmo, Kadek; Suarbawa, Komang Ngurah; Widagda, I Gusti Agung (BULETIN FISIKA; Vol 19 No 2 (2018): BULETIN FISIKA, 2018)
The study is report about to estimate the change of mangrove density level of Ngurah Rai Bali Forest Park from 2014 until 2017 using image of Landsat satellite 8 which was processed with ArcGis software. The density level was determined by using the NDVI method and grouped according to the NDVI range according to the Ministry of Forestry’s rules of 2005. The result shows that in the rare area, the change in the area of density reduced by 23.67 ha, in medium area decreased by 16.74 ha, in the tight area increased by 24.3 ha, and in the total area of mangrove reduced by 16.11 ha. Those results obtained with accuracy of 100 %, 67 %, 93% and 90 % in rare area, medium area, tight area and total area, respectively .